Epistemic justice, institutional transformation and the pursuit of a decolonised African academe - Bonginkosi Hardy Mutongoza (Interdisciplinary Journal of Sociality Studies)
Decolonisation aims to create a more just, inclusive, and equitable academic landscape in Africa by centring marginalised voices and embracing diverse epistemologies. Despite the clamour for truly decolonised universities and the incessant calls for transformation, several studies have demonstrated the pervasiveness of epistemic injustice and the laboured pace at which genuine change is happening. Against this background, this article examines the need for decolonising higher education within the African context, exploring the enduring legacies of colonialism and their continued influence on academic institutions. The article analyses colonial power's psychological, epistemic, and cultural dimensions by drawing on key postcolonial and decolonial theories, including the seminal arguments presented by Said, Fanon, Spivak, and Bhabha. The article also critiques the limitations of postcolonial theory and highlights the emergence of decolonial thought as a more radical approach to dismantling colonial structures. The article identifies four key sites for decolonising the African academe: epistemic, pedagogical, institutional, and research-based. Epistemic decolonisation calls for the reclamation of African ways of knowing and challenges the dominance of Western epistemologies. Pedagogical decolonisation focuses on curriculum reform and the integration of indigenous knowledge. Institutional decolonisation addresses the need to dismantle colonial structures within universities and promote academic autonomy. Research decolonisation advocates for community-centred approaches that empower local voices. Finally, the article emphasises the importance of intersectionality in decolonisation efforts and argues that neglecting the interconnectedness of various forms of oppression risks reproducing existing hierarchies.